Lisina em dietas para alevinos de carpa comum - Signor, Altevir; Bittarello, Alis Correia [UNESP]; Fries, Edionei Maico; Boscolo, Wilson Rogério; Bittencourt, Fábio; Feiden, Aldi (Boletim do Instituto de Pesca, 2017)
The aim of the present study was to determine the lysine requirement of common carp fingerlings. Two hundred and eighty common carp fingerlings, with mean weight and mean length initial of 0.62 ± 0.05 g and 3.38 ± 0.11 cm, respectively were randomly distributed into 28 squares net cages of 150 litres arranged inside a masonry circular tank with water capacity of 25 m-3 (seven treatments and four replications). The fish were fed until apparent satiation, four times per day, with isoproteic and isoenergetic diets supplemented with lysine at 1.58, 1.81, 2.05, 2.29, 2.53, 2.76, and 3.0% of the diet for 57 days. Productive performance, survival rate, and chemical composition of the fish body were evaluated at the end of the study. The data obtained was subjected to regression analysis and, when significantly different (P<0.05), the Tukey multiple comparison test was used. Additionally, linear response plateau (LRP) analysis was performed. Lysine supplementation significantly improved (P<0.05) mean final weight, mean weight gain, and specific growth rate. However, lysine levels above 2.29% compromised the feed efficiency. Lysine requirements of common carp fingerlings were found to be 1.89% of the diet or 4.73% of the crude protein in the diet for obtain better growth.
Lysine in the diet of common carp (Cyprinus carpio) fingerlings
Keywords: Amino acids; Feed; Nutrients; Requirements